Human-in-the-Loop Autonomous Networking: Designing Safe Artificial Intelligence–Assisted Infrastructure Systems - Vijaya Bhaskar Methuku (International Journal of Intelligent Systems and Applications in Engineering, 2026)
Hyperscale network environments have grown far beyond the thresholds where manual operational models remain viable, driving a structural transition from scripted automation toward genuinely autonomous remediation systems that observe, diagnose, and act without waiting for human commands. While this evolution resolves longstanding scalability constraints, it simultaneously introduces categories of systemic risk that have no precedent in deterministic automation architectures. This article proposes a human-in-the-loop autonomy framework built around three interlocking principles: bounded mitigation authority governed by a risk-tiered classification model, confidence-based execution thresholds derived from multi-layer telemetry and signature matching, and a three-stage safety loop that treats rollback capability as a first-class design requirement rather than an afterthought. A controlled testbed evaluation conducted across 127 managed network endpoints over twelve weeks validated the framework’s core safety claims, achieving a 95.3% autonomous success rate, a 4.7% rollback rate with zero cascading failures, and a 19.6x improvement in mean time to remediate relative to manual intervention baselines—representing the first framework to combine risk-tiered authority classification with mandatory pre-execution rollback verification as coequal structural requirements. A structured governance layer ensures that human engineers evolve from reactive troubleshooters into strategic supervisory architects who validate, calibrate, and continuously improve autonomous system behavior. The framework argues that safe autonomy is a structural engineering imperative for the coming decade, not a discretionary enhancement, and that the most resilient infrastructure environments will be those that combine machine speed with human judgment through principled, transparent, and reversible collaboration.